Orientia tsutsugamushi meningitis in a patient with tuberculous meningitis complications—a Case Report - Miao Tan; Hao Zou; MaiQing Yang; Anchun Liu (Frontiers in Medicine)
Scrub typhus (ST) is caused by infection with Orientia tsutsugamushi, transmitted through chigger mite bites, resulting in a febrile disease. Clinical manifestations are complex and may be combined with other microbial infections. This report describes a rare case of scrub typhus meningitis and tuberculous meningitis. The patient presented with fever and chills, and also exhibited a dull reaction upon admission. Timely diagnosis and appropriate antibiotic therapy are critical for preventing complications and reducing mortality. Next-generation sequencing (NGS) provided diagnostic clues, and the diagnosis of scrub typhus meningitis combined with tuberculous meningitis was quickly clarified. The patient’s symptoms were relieved after appropriate treatment. NGS can be a valuable diagnostic tool for detecting early clinical infections.